The Guidelines for the Development of Innovative Leadership of School Administrators under Surin Primary Educational Service Area Office 3 - Aramrueang, Soonthatree; Sitthisuea, Thanyathep; Yodsala, Suphatanakit (Academic MCU Buriram Journal, 2023)
The purposes of this research were: 1) to study the level of innovative leadership of school administrators under Surin Primary Educational Service Area Office 3, 2) to compare the levels of innovative leadership of school administrators under Surin Primary Educational Service Area Office 3, classified by the size of the school, 3) to study the development approaches of innovative leadership of school administrators under Surin Primary Educational Service Area Office 3. The population used in the research was the schools under Surin Primary Educational Service Area Office 3. The sample group. The researcher selected respondents by purposive method consisting and administrators, a total of 292 people. The research tool is a questionnaire with a confidence value of 0.892 the interview form, the development approach assessment form. Research Statistics used were Mean, Standard deviation, One-way Analysis of Variance and Pairwise Test using Scheffe-Method. The research results found that: 1. The current state level of innovative leadership of school administrators under Surin Primary Educational Service Area Office 3, found that an overall was at a high level ( =4.04), when considering each aspect, it was found that all components were at a high level. 2. Overall, it was found that the innovative leadership of school administrators in large schools and medium schools significantly higher than small schools at the .01 level. In part of innovative leadership of school administrators in large and medium schools was not statistically significant. 3. It was found that there are 15 development guidelines. The results of the evaluation of the innovative leadership development guidelines of school administrators under Surin Primary Educational Service Area 3 It was found that the overall suitability was at the highest level ( = 4.58), there was the overall probability was at the highest level ( = 4.58) and there was the overall usefulness was at the highest level ( = 4.58).